2018
DOI: 10.1080/00380768.2018.1525573
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of in situ rainwater harvesting techniques and fertilizer sources on mitigation of soil moisture stress for sorghum (Sorghum bicolor (L.) Moench) in dryland areas of Tanzania

Abstract: Nutrient deficiency, high rate of evapotranspiration, and insufficient and erratic rainfall are the critical challenges for crop production in the dryland areas (DLAs) of Sub-Saharan Africa, including Tanzania, where 61% of arable land is prone to drought. In addressing these challenges, field trials were conducted in central Tanzania to evaluate the interactive effects of ripping and tie-ridges with organic (FYM) and inorganic fertilizers (N) on the mitigation of the critical period of soil moisture stress (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 6 publications
6
23
0
Order By: Relevance
“…Studies by Mishra and Patil (2015), Shamme et al (2016), andSharma andBali (2017) showed a significant positive association between nitrogen and soil moisture on sorghum grain yield. Mahinda et al (2018) also found that the integration of the RWH method and nitrogen application improves crop productivity. The low grain yield response to nitrogen addition in the SC was due to low moisture content evidenced by the low gravimetric water content (Table 2).…”
Section: Grain Yieldmentioning
confidence: 89%
See 4 more Smart Citations
“…Studies by Mishra and Patil (2015), Shamme et al (2016), andSharma andBali (2017) showed a significant positive association between nitrogen and soil moisture on sorghum grain yield. Mahinda et al (2018) also found that the integration of the RWH method and nitrogen application improves crop productivity. The low grain yield response to nitrogen addition in the SC was due to low moisture content evidenced by the low gravimetric water content (Table 2).…”
Section: Grain Yieldmentioning
confidence: 89%
“…Results support work by Nyamadzawo et al (2012 andNyamadzawo et al (2013) who reported water losses up to 50% being lost as runoff from croplands and disposed of through contour channels. The availability of assimilates, which is influenced by soil water availability, is critical for effective grain filling (Mahinda et al, 2018;Mupangwa et al, 2018). Thus, rainwater harvesting structures can sustain crop production during dry spells improving water use efficiency under rain-fed crop production systems in semiarid regions.…”
Section: Grain Yieldmentioning
confidence: 99%
See 3 more Smart Citations